(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
The heterogeneity in the spatial distribution of initial water saturation influences the performance of hot water flooding. The prospect of a reduction in oil recovery arises from the development of viscous instability. In the present study, a numerical simulation model has been developed by coupling heat transport, and multiphase flow in porous media integrated with the non-isothermal flow, and the numerical model has been verified with the existing analytical solution by Buckley and Leverett. The formation of a wavy temperature profile at the condensation front was found with a decreased depth of temperature penetration. The average rise of temperature is drastically affected by the spatial distribution of initial water saturation. The formation of viscous fingering was highly dominating in the reservoir, with initial water saturation randomly distributed and causing the front to move in an irregular pattern from the initial stage of the flooding. The heterogeneous reservoir with initial water distribution showed the earlier formation of viscous fingering than the homogeneous reservoir. The heterogeneity in the spatial distribution of initial water saturation had caused viscous instability, lower viscosity reduction, lower displacement sweeps efficiency, and higher residual oil saturation. The present study is limited to spatial distribution in initial water saturation to a certain degree of heterogeneity. The heterogeneity in the spatial distribution of initial water saturation highly impacted the production performance of hot water flooding. The present study provides an idea for the implementation and future development of hot water flooding in a randomly initial water saturation distributed environment.